Dampak Perubahan Iklim terhadap Keanekaragaman Hayati dan Kesehatan Lingkungan - Acik Ardiansyah Qutbi; Muhammad Sarjan; Taslim Sjah (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2024)
Climate change is an urgent and complex global challenge that not only affects weather patterns and global temperatures but also has a pervasive impact on biodiversity and environmental health worldwide. Melting of polar ice and rising global sea levels are living examples of widespread observable physical effects. Additionally, these changes also alter rainfall patterns, intensifying droughts in some areas while increasing the risk of floods and storms in other areas. The complex interaction of climate change and biodiversity exacerbate conditions by causing disruptions to the life cycles of species, facilitating the spread of invasive species, and increasing the risk of vector diseases. Effective mitigation strategies are needed to reduce greenhouse gas emissions through renewables, maintain and recover natural ecosystems, and strengthen ecosystem adaptation to minimize these adverse effects. International collaboration and policies supported by scientific evidence are key to meeting this global challenge, with the goal of building a more sustainable future for global environment and health.